2022
DOI: 10.1161/hypertensionaha.122.19362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Liquefied Petroleum Gas Stove Intervention on Gestational Blood Pressure: Intention-to-Treat and Exposure-Response Findings From the HAPIN Trial

Abstract: Background: Approximately 3 to 4 billion people worldwide are exposed to household air pollution, which has been associated with increased blood pressure (BP) in pregnant women in some studies. Methods: We recruited 3195 pregnant women in Guatemala, India, Peru, and Rwanda and randomly assigned them to intervention or control groups. The intervention group received a gas stove and fuel during pregnancy, while the controls continued cookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
(91 reference statements)
1
2
1
Order By: Relevance
“…It is equally likely that the so-called 'fuel stacking' practices, as described in previous studies [24][25][26] together with other environmental sources of PM 2.5 such as trash burning may have also increased the exposure levels to PM 2.5 even among households with clean fuels [27,28]. Regarding the association between household air pollution and the categories of blood pressure as defined by the National High Blood Pressure Education Program [29], we found no suggestive statistical relationship between the type of fuel use and any of the stages [20,30]. Our results showed that the risk of an LPG user becoming pre-hypertensive versus having a normal blood pressure was 0.59 (95% CI: 0.31; 0.52, p-value = 0.102).…”
Section: Discussioncontrasting
confidence: 45%
“…It is equally likely that the so-called 'fuel stacking' practices, as described in previous studies [24][25][26] together with other environmental sources of PM 2.5 such as trash burning may have also increased the exposure levels to PM 2.5 even among households with clean fuels [27,28]. Regarding the association between household air pollution and the categories of blood pressure as defined by the National High Blood Pressure Education Program [29], we found no suggestive statistical relationship between the type of fuel use and any of the stages [20,30]. Our results showed that the risk of an LPG user becoming pre-hypertensive versus having a normal blood pressure was 0.59 (95% CI: 0.31; 0.52, p-value = 0.102).…”
Section: Discussioncontrasting
confidence: 45%
“…Additionally, analysis of total air pollution over the study period suggests that the disease fraction attributable to household air pollution could be decreasing in LMICs, possibly because of a reduction in the prevalence of solid-fuel use. The observation that rising ambient pollution, especially in LMICs, could lessen the health benefits of clean energy adoption is consistent with the results of large randomised controlled trials, [5][6][7][8] which have not consistently shown improved health outcomes when clean fuels are used for cooking.…”
Section: Maps Of Solid-fuel Use and Household Air Pollutionsupporting
confidence: 73%
“…reported higher SBP and DBP in the LPG intervention arm as compared with control. 63 We now report that a prenatally introduced LPG stove supported through child age 1 year, but with no evidence of continued use at 4 years of age or exposure differential between groups, was associated with a , or 3%, reduction in DBP relative to children whose mothers used a traditional open fire stove throughout pregnancy. In females, the LPG intervention was associated with a , or 4%, reduction in DBP and a , or 2%, reduction in SBP as compared with control.…”
Section: Discussionmentioning
confidence: 67%